FAKTOR INSTRINSIK MOTIVASI KERJA PEGAWAI DALAM MENINGKATKAN PELAYANAN ADMINISTRASI DI KANTOR KECAMATAN MALUNDA KABUPATEN MAJENE - Nur Fitrah; Muhammad Said Saggaf (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2018)
This study aims to determine the performance of the apparatus in providing services at the Malunda District Office in Majene Regency, as well as any factors that affect the performance of the apparatus in providing services. Data was collected through library studies and field studies using questionnaires, interviews, observation, and documentation. Instrinsic factors that influence the provision of service personnel related to service procedures, the time of completion of services has been running optimally in accordance with the established service procedures by facilitating the provision of services to the community. While other indicators such as facilities and infrastructure still look inadequate in supporting services. The competencies possessed by the authorities are in accordance with the level of education, skills and skills.